Monitoring, liquidity provision and financial crisis risk - B. Gabriela Mundaca (University of Oslo, Department of Economics, 2007)
This paper analyzes central bank policies on monitoring banks in distress when liquidity provisions are conditional on performance and a bad shock occurs. A sequential game model is used to analyze two policies: one in which the central bank acts with discretion and the second in which the optimal monitoring policy rule is made public. The results show that banks exert less effort and take higher risks with discretionary monitoring policy. With public information about monitoring rules, there is more central bank monitoring and less need to provide emergency financing. Public information about monitoring resolves the multiple equilibria that arise with discretion and a unique equilibrium emerges where the probability of banking crisis is reduced.
Keywords: E58; G21; G28; G38; 330; Monitoring; bailouts; banking crises; commitments; conditionality; Geldpolitik; Zentralbank; Bankenkrise; Bankrisiko; Bankenaufsicht; Moral Hazard; Extensives Spiel; Spieltheorie